A novel PTCH1 mutation underlies nonsyndromic cleft lip and/or palate in a Han Chinese family. (9th July 2018) - Zhao, Huaxiang; Zhong, Wenjie; Leng, Chuntao; Zhang, Jieni; Zhang, Mengqi; Huang, Wenbin; Zhang, Yunfan; Li, Weiran; Jia, Peizeng; Lin, Jiuxiang; Maimaitili, Gulibaha; Chen, Feng
Abstract: Objectives: Cleft lip and/or palate (CL/P) is the most common craniofacial congenital disease, and it has a complex aetiology. This study aimed to identify the causative gene mutation of a Han Chinese family with CL/P. Subjects and Methods: Whole exome sequencing was conducted on the proband and her mother, who exhibited the same phenotype. A Mendelian dominant inheritance model, allele frequency, mutation regions, functional prediction and literature review were used to screen and filter the variants. The candidate was validated by Sanger sequencing. Conservation analysis and homology modelling were conducted. Results: A heterozygous missense mutation c.1175C>T in the PTCH1 gene predicting p.Ala392Val was identified. This variant has not been reported and was predicted to be deleterious. Sanger sequencing verified the variant and the dominant inheritance model in the family. The missense alteration affects an amino acid that is evolutionarily conserved in the first extracellular loop of the PTCH1 protein. The local structure of the mutant protein was significantly altered according to homology modelling. Conclusions: Our findings suggest that c.1175C>T in PTCH1 (NM_000264 ) may be the causative mutation of this pedigree. Our results add to the evidence that PTCH1 variants play a role in the pathogenesis of orofacial clefts.